The Effectiveness of Miro Application to Enhance 8th Grade Students’ Writing Skill of Descriptive Text in SMPN 2 Sutojayan - Annisa Nasusianto; Sindhu Rhineksha Mukti; Hesty Puspita Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
English proficiency is vital for academic and professional success in Indonesia, but students often struggle with writing. Descriptive text composition is challenging due to its intricate structure and linguistic elements. To overcome these challenges, the researcher suggests utilizing the Miro Application, a digital whiteboard tool known for fostering interactive collaboration and effectiveness in dynamic learning activities. The study aims to assess Miro's impact on enhancing 8th grade students' descriptive text writing skills at SMP Negeri 2 Sutojayan. The study utilizes a quantitative experimental approach, specifically a pre-experimental design, conducted at SMP Negeri 2 Sutojayan over one month, from November to December 2023. The population includes all 8th grade students, with a purposive sample of 31 students from a single recommended class. This research, conducted with 8th-grade students at SMP Negeri 2 Sutojayan, employed a one-group pre-test post-test design. Data analyses covered normality, homogeneity, and paired sample t-tests. Normality test values (0.095 and 0.088) aligned with good data distribution. Homogeneity test (0.067) affirmed data homogeneity, indicating methodical soundness. The hypothesis test for Miro Application based learning impact yielded a significant result (0.000 < 0.05). Miro Application significantly affected post-test scores, presented digitally via mobile phones. Finally, The Miro Application demonstrated effectiveness in enhancing descriptive text writing skills.